Study of spatial profiles of capacitively coupled VHF H2 plasma by simulation. (9th November 2016) - Chen, Kuan-Chen; Chiu, Kuo-Feng; Ogiwara, Kohei; Su, Li-Wen; Uchino, Kiichiro; Kawai, Yoshinobu
Abstract: The spatial profiles of a VHF H2 plasma (60 MHz) for different discharge gap distances were examined at pressures of 66.7 and 133.3 Pa by two-dimensional simulations using the plasma hybrid code. The electron density had a peak profile, and the maximum density depended on both the discharge gap distance and the pressure. A high-electron-density plasma with a low-electron temperature of approximately 1 eV was predicted by simulation at discharge gap distances of 15 and 20 mm. The plasma potential profile was composed of a plateau at the center and sharp slopes at the two sides. The axial profiles of the H +, H2 +, and H3 + densities were calculated for the discharge gap distances of 10, 15, and 20 mm. It was found that the dominant ion species was H3 + except near the discharge electrode and the H2 + density near the discharge electrode was not negligible compared with the H3 + density at 66.7 Pa.